Parcie Geostatyczne na Tle Doświadczeń - Wierzbicki, W. (Engineering Transactions, 1964)
The problem is that of application of the results of model tests of soil pressure carried out at the IPPT (Institute of Basic Technical Problems), Polish Academy of Sciences, to the computation of real walls. The diagrams of unit pressure z obtained by experiment at the depth x below the embankment are replaced with sinusoids (4) where the parameters zm are equal to the unit bottom of the wall. The diagram of the parameters pressure at the smoothed by the method of least squares, zm obtained from the experiments has been a straight line being obtained. Athough the increases Δa of the direction coefficients of the lines connecting the values of the parameters zm at various levels (Fig. 3) tend to decrease with increasing wall height, the value of 4a is assumed in the computation to be constant for safety reasons. Under such conditions the expression of the sum of terms of the arithmetic progression of which the difference is Δa, leads to the Eq. 12 for zm, for a wall of any height and an expression for total pressure. Some computation examples are given.